SINTESIS ANALOG UK-3A : 6-HIDROKSI-N-FENILNIKOTINAMIDA DAN 6-HIDROKSI-N- FENILPIKOLINAMIDA DAN UJI SITOTOKSISITAS SECARA IN VITRO TERHADAPSEL KANKER MURINE LEUKEMIA P388 - Febriyanti, Lilis; Hanafi, Muhammad; Hayun, Hayun (Jurnal Farmasi Indonesia, 2018)
The Novel compound of analog UK-3A defined as HF-1 (6-hydroxy-N-phenylnicotinamide) and HF-2 (6-hydroxy-N-phenylpicolinamide)was successfully synthesized by amidation reaction of aromatic carboxilyc acids and primary amine by adding the activator of DCC (dicyclohexylcarbodiimide), catalyst DMAP (4-dimethyl aminopyridine, and DMSO (dimethyl sulfoxide) as the solvent. Reaction run for 24 hours in 55oC. Result shows yield of HF-1 as much as 52%, and for HF-2 is 16%. The analogue compounds structure of UK-3A were characterized by spectrophotometer FT-IR, LCMS, and NMR. Citotoxicity assay against Murine Leukemia cells of HF-1 and HF-2 by MTT (3-(4,5-dimethylltiazo-2-yl-) 2,5-diphenyltetrazolium bromide) assay. The result of bioassay showed IC50(inhibitory concentration)value 71 µg/mL and 63 µg/mL for HF-1 and HF-2 respectively. It informed that the analogue compounds have lower activity than UK-3A compound which has IC50 value 38 µg/mL.